Cognitive dissonance in philological perspective - Tatiana V. Drozdova; Olga D. Vishnyakova; Elizaveta A. Vishnyakova (Вестник Самарского университета: История, педагогика, филология, 2022)
The article deals with the problem of cognitive dissonance that represents itself as the discrepancy between cognitive bases of communicants, exteriorized at the level of language. Cognitive dissonance may be caused by various reasons, including linguistic ones connected with the inappropriate choice of language means and communicative strategies, as well as social and other extralinguistic factors, which refer to semantic and conceptual incompatibility actualized in human intercourse. As the result, in most cases the communicants tend to eliminate situations of dissonance by various means appropriate and achieve the state of consonance. Within the domain of literary space the potential of language that refers to cognitive dissonance emergence and its further annihilation if possible may be used to produce a certain stylistic effect and produce the aesthetic impact necessary as well as become intellectual stimulus for further inference. The analysis of cognitive dissonance situations represented in the artistic discourse has shown that in the domain of verbal art their creative abilities, both in terms of naturally occurred and intentionally provoked precedents, represented via means of language, can be exploited for the sake of constructing the specific atmosphere of virtual space and artistic images creation, which contributes to the author’s message successful transfer to the reader or listener. This may be confirmed by the results of linguopoetic and linguostylistic investigations, as well as profound philological context analysis, based on integrating linguistic knowledge with knowledge of the world, in which language data are prioritized.